PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Rahma Maulidia; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of the structure of good corporate governance on the disclosure of corporate social responsibility in financial companies listed on the Indonesian stock exchange in 2018-2020. The independent variables in this study are managerial ownership, institutional ownership, audit committee, and the size of the board of commissioners, while the dependent variable is the disclosure of corporate social responsibility in financial companies listed on the Indonesian stock exchange in 2018-2020. This type of research is quantitative research, because the data used are in the form of numbers and numbers. The source of data in this study is secondary data obtained from the annual reports of financial companies listed on the Indonesia stock exchange in 2018-2020 which are taken from the website www.idx.co.id. The population in this study are financial companies listed on the Indonesian stock exchange during 2018-2020. The data collection method used purposive sampling technique. The hypotheses were tested using descriptive statistical analysis, normality test, classical assumption test, multiple linear regression analysis test, and hypothesis testing using SPSS Version 26. The results showed that managerial ownership variable had a positive and significant effect on corporate social responsibility disclosure (0.013 < 0.05), while the institutional ownership variable has no effect on the disclosure of corporate social responsibility (0.453 > 0.05), the audit committee variable has no effect on the disclosure of corporate social responsibility (0.373 > 0.05), and the variable size of the board of commissioners has a positive and positive effect. significant to the disclosure of corporate social responsibility (0.006 <0.05).Keywords: corporate social responsibility, managerial ownership, institutional ownership, audit committee, board of commissioners size.